Municipal caravan parks in South Africa: geography, management and planning - Rogerson, Christian M.; Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2020)
Caravan parks are a largely overlooked theme in tourism scholarship. In South Africa, as in several other countries, local governments assumed an historical role in the establishment of caravan parks. Municipal caravan parks are assets which could be leveraged for tourism growth and local development. The planning and management of caravan parks in South Africa can be understood as an element of asset management by local governments. It is shown that across most of South Africa municipal ownership of caravan parks is of declining significance as compared to the dominance of privately owned parks. The coastal province of the Western Cape is the biggest focus for caravanning and for the location of all caravan parks, including for the largest cluster of municipal owned caravan parks in South Africa. Research interviews were conducted with local stakeholders concerning contemporary planning and management of caravan parks. The results reveal that most local municipalities currently are struggling to manage appropriately and optimally maximise for local development the operations of municipal caravan parks. Many municipalities are considering different options for privatisation through selling off or leasing parks to private sector investors.